THE IMPACT OF RETAIL IT APPLICATIONS ON EFFECTIVE STORE OPERATIONS AMONG FAMILY RETAIL STORES IN SABAH - Md Zaki Bin Muhamad Hasan; Erdawati Binti Suda (International Journal of Accounting, Finance and Business, 2022)
This study investigates the relationship between factors that influence effective store operation among retailers in Sabah. Conceptual frameworks of different variables such as store, order management and inventory control have been studied to measure effective store operation. Factors that influence customer satisfaction with IT retail stores are important to identify to ensure that it meets the knowledge of retailers. This study was conducted using a quantitative research approach. A total of 384 questionnaires were distributed to the targeted respondents i.e., Retailers who run family grocery store businesses and the feedback will be used for data analysis. The findings of the study found that order management and inventory control factors have a significant relationship with effective store operation while store factors clearly do not affect effective store operation. The results of this paper will also show the importance of stores, order management and inventory control to assist the management of retail stores to increase the profit rate and convenience of customers. The lack of cooperation from third parties made it difficult for this study to find respondents and took a long time in collecting data.